2012
DOI: 10.1007/s00198-012-2057-z
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and its relationship with bone mineral density in middle-aged and elderly European men

Abstract: Sarcopenia is associated with low BMD(a) and osteoporosis in middle-aged and elderly men. Further studies are necessary to assess whether maintaining muscle mass contributes to prevent osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
172
6
21

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(216 citation statements)
references
References 54 publications
17
172
6
21
Order By: Relevance
“…On the other hand, Janssen et al (2002) reported a large-scale cross-sectional study using bioelectric impedance analysis and found that the prevalence of severe sarcopenia was less than 5 % for men and women aged 49 years or younger and approximately 10 % for men and women aged 70 years or older. In the present study, the prevalence rate of severe sarcopenia was relatively higher in nonobese men compared with those of the previous studies and was consistent with previous studies in women (Baumgartner et al 1998;Bijlsma et al 2013;Chien et al 2008;Dufour et al 2012;Janssen et al 2002;Kim et al 2012;Masanes et al 2012;Rolland et al 2003;Tanimoto et al 2012;Tichet et al 2008;Verschueren et al 2012). Taken together with previous studies (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, Janssen et al (2002) reported a large-scale cross-sectional study using bioelectric impedance analysis and found that the prevalence of severe sarcopenia was less than 5 % for men and women aged 49 years or younger and approximately 10 % for men and women aged 70 years or older. In the present study, the prevalence rate of severe sarcopenia was relatively higher in nonobese men compared with those of the previous studies and was consistent with previous studies in women (Baumgartner et al 1998;Bijlsma et al 2013;Chien et al 2008;Dufour et al 2012;Janssen et al 2002;Kim et al 2012;Masanes et al 2012;Rolland et al 2003;Tanimoto et al 2012;Tichet et al 2008;Verschueren et al 2012). Taken together with previous studies (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The association between sarcopenia and bone mass demonstrated in this study is consistent with the hypothesis of previous studies showing a reduction in osteogenic effect due to a minor mechanical stimulation imposed on the bone structure by reducing the muscle and muscle function (4,6,15). Another point would be the reduction of the mechanical stimuli from less physical activity due to a lower functional capacity of the elderly caused by sarcopenia (12).…”
Section: Sarcopenia and Osteoporosis In Mensupporting
confidence: 91%
“…Sarcopenia has emerged as an important risk factor for osteoporosis (3,4). In addition to increasing falls risk, sarcopenia might also decrease bone strength by reducing mechanical loading to the skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia has been found to be an independent predictor of physical disability and development of mobility disorders, as well as reduced bone mineral density [27,34,35]. Diagnosis is usually through identifying loss of lean body mass (e.g.…”
Section: Development Of Frailtymentioning
confidence: 99%